2013
DOI: 10.1111/tesg.12008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Concentration in the Irish Pharmaceutical Industry: The Role of Spatial Planning and Agglomeration Economies

Abstract: This paper explores the idea that spatial planning-triggered satellite industrial platform-type concentrations may, over time, automatically gain the capacity to generate substantial agglomeration economies and ultimately transform into entities capable of stimulating self-perpetuating growth. Applying the lexicon of agglomeration theory, the idea is explored in the context of the spatial dynamics of the pharmaceutical industry in Ireland. Spatial concentration indices indicate a particularly high level of spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In the absence of inter-firm transactions, the efficiency gains related to the pool of labour may well be the only significant agglomeration advantage operative in such concentrations. These advantages may take the forms of efficiency gains due to a pooled market for workers and a varied set of input and service suppliers, benefiting a whole range of sectors (Egeraat, 2006). Such urbanization economies (i.e., efficiencies that result from the agglomeration of many different kinds of activities in a given region) can be expected to play some positive spillover role and empirical studies support this conclusion.…”
Section: Hypothesesmentioning
confidence: 51%
“…In the absence of inter-firm transactions, the efficiency gains related to the pool of labour may well be the only significant agglomeration advantage operative in such concentrations. These advantages may take the forms of efficiency gains due to a pooled market for workers and a varied set of input and service suppliers, benefiting a whole range of sectors (Egeraat, 2006). Such urbanization economies (i.e., efficiencies that result from the agglomeration of many different kinds of activities in a given region) can be expected to play some positive spillover role and empirical studies support this conclusion.…”
Section: Hypothesesmentioning
confidence: 51%
“…The spatial configuration of the industry is characterized by a high level of concentration, involving three substantial concentrations (in Cork, Dublin and Waterford) although pharmaceutical plants are operating in several other locations in the country. Detailed qualitative research on the Cork concentration (Van Egeraat and Curran ), showed that the pharmaceutical companies within that concentration utilized very few raw material input suppliers, even at the national level, supporting the idea of highly mobile pecuniary externalities (Phelps et al ). The Cork‐based pharmaceutical firms did benefit from proximity to a grouping of engineering companies.…”
Section: Resultsmentioning
confidence: 93%
“…Once again, the overlapping labour field methodology not only refines the geographical extent of the concentrations but also identifies an additional discrete substantial pharmaceutical concentration around Waterford. This method provides a precise depiction of the empirical reality of two discrete substantial pharmaceutical concentrations in the south of Ireland, one focused on drug substance chemical synthesis (around Cork) and one on drug product manufacturing (around Waterford) (see Van Egeraat and Curran ).…”
Section: Substantial Concentrations In the Republic Of Irelandmentioning
confidence: 99%
“…Measure study on industrial agglomeration level and single industrial concentration measurement method has a lot of literature research; there are mainly location entropy (Xie et al, 2015) [24], industrial geographical concentration (Chris and Declan, 2013) [25], Herfindahl-Hirschman index (Bruckmann, 1971) [26], locational Gini-coefficient (Dagum, 1986) [27], E-G index (Ellison and Glaeser, 1999) [28], multivariable intelligent analysis (Su et al, 2019; Su et al, 2020) [29,30], K function (Ripley, 1977) [31], D-O index (Yuan et al, 2014) [32], Moran's I (Moran, 1950) [33], and Standard Deviational Ellipse (Wong, 1999) [34]. e research on common agglomeration measurement method is relatively late.…”
Section: Introductionmentioning
confidence: 99%